Agriculture and Public Information in Post-War Bosnia and Herzegovina - Heijman, W. J. M.; Moll, H. A. J.; Wals, A. E. J. (Acta Agraria Debreceniensis, 2002)
Since the Dayton Agreement on Bosnia of 1995 there is peace between Croats, Bosnians and Serbs. Whether this is a lasting situation remains to be seen (de Rossanet, 1997). Pessimists refer to Huntington’s “Clash of Civilizations” and argue that because Bosnia is situated on the fault line of the Western and Orthodox civilizations and on top of that has a large muslim minority a new war can not be avoided (Huntington, 1997). Others don’t accept this and are of the opinion that rational governance will overcome the problems of the multicultural society. In this view the restoration of the country’s economy is a major priority. However, on the long run, a peaceful outcome is not to be taken for granted. At present, the international community represented by the Office of the High Representative (OHR) in Bosnia and Herzegovina (BiH) controls the political situation and the three ethnic groupes are forced to cooperate. To sustain a lasting peace in the future without the guidance of the OHR the reconstruction of the Bosnian economy starting with the agricultural sector is a precondition. This paper reports on a quick scan carried out in the period 15-19 April, 2002, in order to evaluate the possibilities of the agricultural sector as an economic booster in the post war situation. The quick scan was necessary to evaluate and give advise with respect to the plans of the OHR to engage in a public information campaign in order to stimulate the transformation of subsistence farming into commercial agriculture, and to encourage young urban Displaced Persons (DP’s) to consider life as a farmer as an option for their future. The campaign will include a number of sub-regional radio and television series, and a booklet and videos for distribution among the target groups.